2009
DOI: 10.1073/pnas.0812259106
|View full text |Cite|
|
Sign up to set email alerts
|

CIB1 functions as a Ca 2+ -sensitive modulator of stress-induced signaling by targeting ASK1

Abstract: Calcium and integrin binding protein 1 (CIB1) is a Ca 2+ -binding protein of 22 kDa that was initially identified as a protein that interacts with integrin α IIb . Although it interacts with various proteins and has been implicated in diverse cellular functions, the molecular mechanism by which CIB1 regulates intracellular signaling networks has remained unclear. We now show that, by targeting apoptosis signal-regulating kinase 1 (ASK1), CIB1 negatively regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 39 publications
2
57
0
Order By: Relevance
“…The molecular mechanism behind this control is poorly understood, although it has been suggested that it involves the transcription factor osterix (26). As this manuscript was being prepared, a publication (27) showed that calcium and integrin binding protein (CIB), which we had previously identified as an interacting partner of Nbr1 (28), functions as a Ca 2+ -sensitive modulator of stress-induced signaling by targeting apoptosis signalregulating kinase 1 (ASK1), a MAPK kinase kinase in JNK and p38 MAPK signaling pathways, which may fit with the function of Nbr1 in regulating p38 MAPK activity. Furthermore, Nbr1 was recently shown to modulate FGF receptor signaling through interaction with Spred2 (29), and with its previously well-documented involvement in titin kinase signaling in muscle (30), Nbr1 is now becoming recognized as a regulator of diverse cellular kinase signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism behind this control is poorly understood, although it has been suggested that it involves the transcription factor osterix (26). As this manuscript was being prepared, a publication (27) showed that calcium and integrin binding protein (CIB), which we had previously identified as an interacting partner of Nbr1 (28), functions as a Ca 2+ -sensitive modulator of stress-induced signaling by targeting apoptosis signalregulating kinase 1 (ASK1), a MAPK kinase kinase in JNK and p38 MAPK signaling pathways, which may fit with the function of Nbr1 in regulating p38 MAPK activity. Furthermore, Nbr1 was recently shown to modulate FGF receptor signaling through interaction with Spred2 (29), and with its previously well-documented involvement in titin kinase signaling in muscle (30), Nbr1 is now becoming recognized as a regulator of diverse cellular kinase signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CIB1 is known to interact with a variety of kinases, including ASK1 (34). This fact is relevant because we and others have reported that cADPR synthesis in sea urchin eggs is activated by a cGMPdependent phosphorylation process (35,36).…”
Section: Visualization Of Intracellular Interaction Of Cd38 With Cib1mentioning
confidence: 92%
“…The 13 C, 2 H, 15 N-uniformly labeled sample was expressed and purified according to an established protocol (12), and this sample was used to acquire the backbone 1 7 -glucose; this sample was used to record the CIB1 backbone CPMG-relaxation dispersion spectra. The synthetic 26-residue ␣IIb peptide (Ac-LVLAMWKVGFFKRNRP-PLEEDDEEGQ-OH) is the same as used in earlier studies (12), and it corresponds to amino acids 983-1008 of the platelet integrin ␣IIb subunit, with Gln-1008 as the C-terminal residue.…”
Section: Methodsmentioning
confidence: 99%